Glaube, Wissenschaft, Sprache Eine diachronische Studie zur protestantisch-theologischen Fachsprache im 20. Jahrhundert - Gerdes, Joachim (Deutsch als Fremd- und Fachsprache, 2022)
This publication provides a diachronic overview of the main tendencies in Protestant theological jargon and academic language from the nineteenth to twenty-first centuries from a Germanist-linguistic perspective. Using analyses of special linguistic features in the works of representative authors and in predominant academic currents, it thoroughly illuminates the role of linguistic phenomena in Protestant theological jargon.